Does the size structure of the littoral community reflect water level fluctuations in shallow waterbodies? - Maria Špoljar (Elsevier, 2021)
The littoral zone of shallow water bodies (SWB) is highly susceptible to water level fluctuations (WLF) caused by ongoing climate-related hydrologic regime changes. The present study assessed the macrozoobenthos structure in the littoral of three temperate SWB after pronounced WLF and accompanying reduction of macrophyte coverage caused by excessive precipitation. The three SWB differed in environmental conditions – S1 (transparent lake covered with submerged macrophytes dominated by Ceratophyllum demersum); S2 (turbid lake without macrophyte coverage) represented the two interconnected backwater basins of the Sutla River watershed; and SK (Škrčev kut oxbow; highly turbid lake sparsely covered by floating-leaved Nuphar lutea) located in the Krapina River watershed (Croatia). With the aim to disentangle the littoral food web structure, and interactions among environmental conditions as well as structural and functional traits of the littoral community within the three SWB, the macrozoobenthos functional traits, trophic guilds and body size were correlated with the littoral environmental conditions, and with the traits of the potential macrozoobenthos prey (zooplankton) and predators (fish). Our results suggest that the littoral macrozoobenthos assemblage responded to the water level increase mainly by the decline of macroinvertebrate diversity and abundance. Due to loss of habitat heterogeneity, in general, larger-sized macroinvertebrates dominated the littoral zone of turbid SWB, particularly with high WLF, while smaller-sized detritivores and grazers prevailed in the littoral zone of the transparent SWB covered by submerged macrophytes. The correlations between different macrozoobenthos, zooplankton and fish size classes indicated that the larger-sized predatory macroinvertebrates prey on smaller-sized zooplankters and avoid predation of mid-sized fish. On the other hand, the abundance of smaller-sized macroinvertebrate detritivores and grazers, which were significantly correlated with concentrations of suspended detritus and algae, prevailed in the SWB covered by submerged macrophytes. Within the macrophyte-covered littoral habitats, macroinvertebrates coexisted with small-sized fish and zooplankters as well as with large-sized pelagic zooplankters, likely seeking shelter from fish. We assume that the increased abundance of larger-sized specimens affected macroinvertebrates and fish within the littoral community upon water level increase. Such a pattern could be recognized as an indicative trait in the evaluation of ecosystem functioning. Furthermore, we conclude that the structural and functional traits of the SWBs’ littoral communities could help us predict the ecological consequences of the climate-induced WLF.